2021
DOI: 10.1242/jeb.242512
|View full text |Cite
|
Sign up to set email alerts
|

The early life of king penguins: ontogeny of dive capacity and foraging behaviour in an expert diver

Abstract: The period of emancipation, when juvenile seabirds change from a terrestrial existence to a life at sea, is associated with many challenges. Apart from finding favourable foraging sites, they have to develop effective prey search patterns and physiological capacities that enable them to capture sufficient prey to meet their energetic needs. Animals that dive to forage, like king penguins (Aptenodytes patagonicus), need to acquire an adequate breath-hold capacity, allowing them to locate and capture prey at dep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 73 publications
(127 reference statements)
0
1
0
Order By: Relevance
“…So far, cross-sectional studies have hypothesized (and mostly confirmed) that foraging performance increases with age, at least in the younger age classes (e.g. [57]). This might be due to the selective disappearance of under-performing individuals rather than, or in addition to, learning maturation processes.…”
Section: Introductionmentioning
confidence: 99%
“…So far, cross-sectional studies have hypothesized (and mostly confirmed) that foraging performance increases with age, at least in the younger age classes (e.g. [57]). This might be due to the selective disappearance of under-performing individuals rather than, or in addition to, learning maturation processes.…”
Section: Introductionmentioning
confidence: 99%